ANALYSIS CHARACTERISTICS REFUSE DERIVED FUEL (RDF) BRIQUETTES FROM MIXTURE RICE STRAW AND CARDBOARD WASTE WITH VARIATION RATIO MATERIAL AS ENERGY ALTERNATIVE - LD Muhammad Raldi; Setia Damayanti; La Ode M. Firman (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
This study aims to analyze the characteristics of Refuse Derived Fuel (RDF) briquettes produced from a mixture of rice straw waste and cardboard waste with varying composition ratios as an alternative energy source. The research employed a quantitative approach using an experimental method through briquette production and laboratory testing. The composition variations used were 80:20 and 70:30 (straw: cardboard). The parameters analyzed included calorific value, moisture content, ash content, volatile matter, and fixed carbon through proximate and ultimate analysis. The results showed that the 70:30 composition produced the highest calorific value of 2,029.34 kcal/kg compared to 1,742.03 kcal/kg for the 80:20 composition. In addition, the 70:30 composition has lower moisture and ash content, as well as higher volatile matter and fixed carbon. Based on Waste to Energy (WtE) feasibility standards, both variations met the criteria for calorific value, moisture content, and fixed carbon, but did not meet the standards for ash content and volatile matter. Overall, the 70:30 composition demonstrated more optimal performance as a waste-based alternative fuel. This study contributes to the utilization of biomass and solid waste as sustainable energy sources.